Access to Environmental Cognitive Alternatives Predicts Pro-Environmental Activist Behavior. Issue 3 (April 2022) - Wright, Joshua D.; Schmitt, Michael T.; Mackay, Caroline M. L.
We expand on the plausible role of access to cognitive alternatives to the environmental status quo (i.e., the ability of people to imagine what a sustainable relationship with nature would look like) in motivating pro-environmental collective action. Using a representative sample of Canadians on age, gender, and ethnicity ( N  = 1, 029) we evaluate the associations between access to environmental cognitive alternatives, politicized environmental identity, and willingness to engage in pro-environmental activist behavior. Additionally, we move beyond self-reported behavior by giving participants the opportunity to write and sign a pro-environmental letter to the Canadian Minister of the Environment and Climate Change. Our results suggest that access to cognitive alternatives is associated with stronger politicized environmental identity, greater willingness to engage in pro-environmental activist behavior, and increased likelihood of writing and signing a pro-environmental letter. All methods and analyses follow our preregistration and all materials and data are openly available.